Public Wage Bills in the Middle East and Central Asia - Tamirisa, Natalia (Departmental Papers; Departmental Paper ;, 2018)
Analysis of policies for managing public sector wage bills in the Middle East and Central Asia region. While some work has been done recently at the Fund on issues related to government employment and compensation, to our knowledge, this is the first study to systematically examine, with a focus on the Middle East and Central Asia region, the recent trends and drivers of public wage bills in the region and to identify key policy implications.